Colorimetric Approach for Nucleic Acid Salmonella spp. Detection: A Systematic Review - Asma Nadia Ahmad Faris; Mohamad Ahmad Najib; Muhammad Najmi Mohd Nazri; Amir Syahir Amir Hamzah; Ismail Aziah; Nik Yusnoraini Yusof; Rohimah Mohamud; Irneza Ismail; Fatin Hamimi Mustafa (MDPI, 2024)
Indexed by WOS/Scopus/ERA